Regulation of groundwater arsenic concentrations in the Ravi, Beas, and Sutlej floodplains of Punjab, India. (1st May 2020) - Kumar, Anand; Singh, Chander Kumar; Bostick, Benjamin; Nghiem, Athena; Mailloux, Brian; van Geen, Alexander
Highlights: Proportion of high As wells of Ravi floodplain is higher than that of Beas and Sutlej. As levels in aquifer sands are an order of magnitude higher than the crustal average. High As intervals in groundwater correspond to intervals of high As in aquifer sands. Abundant nitrate and sulfate in groundwater suggest oxidation of As-sulfide minerals. Testing cuttings of aquifer sands for As with field kit can help install safe wells. Abstract: Recent testing has shown that shallow aquifers of the Ravi River floodplain are more frequently affected by groundwater arsenic (As) contamination than other floodplains of the upper Indus River basin. In this study, we explore the geochemical origin of this contrast by comparing groundwater and aquifer sand composition in the 10–30 m depth range in 11 villages along the Ravi and adjacent Beas and Sutlej rivers. The drilling was preceded by testing wells in the same villages with field kits not only for As but also for nitrate (NO3 – ), iron (Fe), and sulfate (SO4 2− ). Concentrations of NO3 – were ≥ 20 mg/L in a third of the wells throughout the study area, although conditions were also sufficiently reducing to maintain > 1 mg/L dissolved Fe in half of all the wells. The grey to grey-brown color of sand cuttings quantified with reflectance measurements confirms extensive reduction of Fe oxides in aquifers of the affected villages. Remarkably high levels of leachable As in the sand cuttings determined with the field kit and As concentration up to 40 mg/kg measured by X-ray fluorescence correspond to depth intervals of high As in groundwater. Anion-exchange separation in the field and synchrotron-based X-ray spectroscopy of sand cuttings preserved in glycerol indicate speciation in both groundwater and aquifer sands that is dominated by As(V) in the most enriched depth intervals. These findings and SO4 2− concentrations ≥ 20 mg/L in three-quarters of the sampled wells suggest that high levels of NO3 –, presumably from extensive fertilizer application, may have triggered the release of As by oxidizing sulfide-bound As supplied by erosion of black shale and slate in the Himalayas. Radiocarbon dating of sub-surface clay cuttings indicates that multiple episodes of inferred As-sulfide input reached the Ravi floodplain over the past 30 kyr. Why the other river basins apparently did not receive similar inputs of As-sulfide remains unclear. High NO3 – in groundwater may at the same time limit concentrations of As in groundwater to levels lower than they could have been by oxidizing both Fe(II) and As(III). In this particular setting, a kit can be used to analyze sand cuttings for As while drilling in order to target As-safe depths for installing domestic wells by avoiding intervals with high concentrations of As in aquifer sands with the well screen.